OPTIMASI RUTE PANDUAN INFORMASI LOKASI WISATA MENGGUNAKAN ANT COLONY SYSTEM PADA KOTA BATAM - alfannisa annurrallah fajrin; Delia Meldra (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2019)
The number of tourists visiting the city of Batam both domestic and foreign tourists to spend their vacation time because the cost of living and goods are cheaper than other areas because batam is an FTZ area (free tax Zone). So that the city of Batam has become a shopping paradise for the people around Batam or outside Batam. Batam itself has several shopping destinations and places to visit for tourists. With the abundance of tourist destinations in the city of Batam, both shopping and nature tourism, it is not uncommon for tourists to experience various problems in visiting the country, one of the simple problems experienced is the problem of time and cost efficiency in conducting tours to the city of Batam. The problem that we can solve in this research is to help tourists or tourists not experience difficulties when visiting tourist attractions in Batam by using the ant colony algorithm in efficient path selection. The Waterfall Model in SDLC is a process that will be used in this study to get the best results.